2017
DOI: 10.1016/j.intmar.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Second Person Pronouns Enhance Consumer Involvement and Brand Attitude

Abstract: Online brand messaging, e.g., blogging or posting on social media platforms, has an important role in digital marketing strategy. Such messaging is largely text based and provides an opportunity for brands to interact with many consumers simultaneously. The marketing literature, however, has yet to provide sufficient guidance on effective online brand messaging strategies. In particular, research has yet to address how the inclusion of second person pronouns in online brand messaging affects relevant consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 36 publications
4
90
1
7
Order By: Relevance
“…To digital marketers, enhancing consumer engagement with brand posts on social media is both vital and challenging [2][3][4]. Consumer engagement with brand posts is positively related with: brand awareness, preference, and consideration [5][6][7][8]; brand equity [5,9]; and brand performance (e.g., sales, new customer acquisition, brand value, etc.) [2,7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To digital marketers, enhancing consumer engagement with brand posts on social media is both vital and challenging [2][3][4]. Consumer engagement with brand posts is positively related with: brand awareness, preference, and consideration [5][6][7][8]; brand equity [5,9]; and brand performance (e.g., sales, new customer acquisition, brand value, etc.) [2,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although academic research suggests that marketers can strategically design brand posts that improve consumer engagement, it is not clear what contents work better for which brand and in what way [12]. While previous research in this area has mainly focused on specific brand post characteristics, such as content type, media type, and post timing, few of them has examined the language used by brand [6,12,15]. Arguably, as a critical medium that communicates brand meanings, language plays a significant role in the underlying processes of consumers identifying, experiencing, integrating, signifying, and connecting with brands and affects consumers' responses to brands in terms of perception, memory, attitude, as well as behavior [16].…”
Section: Introductionmentioning
confidence: 99%
“…), and within a variety of contexts (e.g., single/multiple industries, B2B/B2C, product/service, etc.) (see 5,6,8,10,13,14,[16][17][18][19][20][21][22][23][24][25][26]. Slightly differing in the research design (e.g., sample size and variable operationalization), previous research is mainly rooted in traditional advertising literature and marketing communication theory and dependent on the field study method that uses manual content analysis to analyze data collected from Facebook brand pages.…”
Section: Previous Research On Consumer Engagement With Brand Posts Onmentioning
confidence: 99%
“…Khan et al [37] found that the impacts of content type and media type of brand posts on consumer engagement vary across different cultures. Cruz, Leonhardt, & Pezzuti [6] found that the relationship between second person pronouns usages in online brand messaging and consumer engagement is moderated by individual levels of collectivism. Specifically, the presence (vs. absence) of second person pronouns in online brand messaging increases engagement only for consumers that are lower (vs. higher) in collectivism.…”
Section: Research Stream 2: Re-consider the Consumer Engagement As A mentioning
confidence: 99%
See 1 more Smart Citation